PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI ANDROID MENGGUNAKAN POWERPOINT ISPRING PADA MATERI TEORI KINETIK GAS - Elia Maryam Ramadani; Aripin Aripin; Rifaatul Maulidah (Universitas Labuhanbatu, 2022)
This study aims to develop an android application-based learning media using powerpoint ispring on gas kinetic theory material to describe the level of validity and practicality. This study uses research and development methods with the ADDIE development model but only carried out 4 stages, namely Analysis, Design, Development, and Implementation. The results of the validation of learning media that have been developed to develop learning media based on media experts are 4.25 with a very good category, material experts are 4.38 with very good categories, digital experts are 4.23 with very good categories, and experts are 4 ,2 with good category. The learning media that has been developed was tested on 101 students and 2 educators of XI MIPA SMAN 1 Taraju as research subjects and produced product practicality data based on the results of student responses, namely 4.52 with a very good category and the teacher's response being 4.5 with a category very good. Thus, android application-based learning media is suitable for use in physics learning.Keywords: Learning Media; Android; Powerpoint Ispring; Kinetic Theory of Gas